Prevalence of celiac autoimmunity in children and adolescents with type 1 diabetes mellitus in a high complexity hospital in Colombia (2018)
ABSTRACT: Background: The prevalence of celiac disease in patients with type 1 diabetes mellitus is 5 to 10 times higher than in the general population. However, diagnosis is difficult given that patients are asymptomatic or with nonspecific symptoms and are confused with poor glycemic control or thyroid comorbidity. Objective: To assess the prevalence of celiac autoimmunity in children and adolescents diagnosed with type 1 diabetes mellitus and to identify the clinical profile of patients with celiac autoimmunity. Methods: One hundred patients with type 1 diabetes mellitus under 18 years, who consulted the department of pediatric endocrinology at Hospital Pablo Tobón Uribe – Medellin, between May and December 2015, were included. The concentration of antibodies, anti-tissue transglutaminase IgA, and total immunoglobulin A were measured in all patients; also a survey of signs and symptoms of celiac disease was applied. Results: Patients were aged between 3 and 17 years. Four had celiac autoimmunity evidenced by positive anti-tissue transglutaminase IgA. The clinical profile of patients with celiac autoimmunity was patient